Japanese cinema goes global : filmworkers' journeys - Tezuka, Yoshiharu (TransAsia--screen cultures., 2012)
With careful research and unique first-person observations drawn from years of working within the international industry of Japanese film, the author examines how different generations of Japanese filmmakers engaged and interacted with the structural opportunities and limitations posed by external forces.